2004
DOI: 10.1073/pnas.0305905101
|View full text |Cite
|
Sign up to set email alerts
|

Dominant inhibitory adipocyte-specific secretory factor (ADSF)/resistin enhances adipogenesis and improves insulin sensitivity

Abstract: Adipocyte-specific secretory factor (ADSF)͞resistin is a small cysteinerich protein secreted from adipose tissue that belongs to a gene family found in inflammatory zone (FIZZ) or found in resistin-like molecule (RELM). ADSF has been implicated in modulating adipogenesis and insulin resistance. To examine the long-term function of ADSF in adipogenesis and glucose homeostasis, we constructed an expression vector for a dominant inhibitory form of ADSF by fusing it to the human IgG␥ constant region (hFc). ADSF-hF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
80
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 40 publications
10
80
0
1
Order By: Relevance
“…Considerable debate exists regarding the role of resistin in the pathophysiology of insulin resistance in humans and animals and as to whether resistin acts primarily in muscle, liver or fat [2,3,5,[29][30][31][32]. However, several studies provide convincing evidence for an effect of resistin in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considerable debate exists regarding the role of resistin in the pathophysiology of insulin resistance in humans and animals and as to whether resistin acts primarily in muscle, liver or fat [2,3,5,[29][30][31][32]. However, several studies provide convincing evidence for an effect of resistin in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Resistin caused insulin resistance at the level of both skeletal muscle (decreased insulin-stimulated glucose infusion during clamp) and liver (attenuation of suppression of hepatic glucose output) [31]. Furthermore, preventing resistin action in transgenic mice expressing a dominant inhibitory version of the protein improved insulin sensitivity and glucose tolerance in mice [5]. A recent elegant study where adipocytes transfected in vitro to express resistin were surgically inserted into mice showed that these mice then exhibited high plasma resistin levels [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, ablation of the retn gene or reduction in resistin protein through antisense oligonucleotide treatment improves insulin sensitivity through AMPK activation (86,87). Resistin inhibits adipogenesis, whereas the loss of resistin function increases body weight and fat and enhances insulin sensitivity (88,89). Thus, resistin has significant roles in energy and glucose homeostasis.…”
Section: Role Of Leptin In Famine and Feastmentioning
confidence: 99%
“…Neutralization of endogenous resistin by antibodies improved insulin sensitivity in mice with diet-induced obesity (1). An inhibitory effect of resistin on adipose conversion could also be demonstrated in vitro (3,4). In addition, it was also suggested that resistin may be involved in inflammation due to its homology to FIZZ1 (2).…”
Section: Introductionmentioning
confidence: 81%